2001
DOI: 10.1136/heart.85.6.623
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification in unstable angina and non-Q wave myocardial infarction using soluble cell adhesion molecules

Abstract: Objective-To assess prospectively the prognostic value of soluble cellular adhesion molecules (CAMs) in patients with unstable angina and non-Q wave myocardial infarction and to compare their prognostic accuracy with that of C reactive protein (CRP). Design and setting-Prospective observational study of patients presenting acutely with unstable angina and non-Q wave myocardial infarction to a single south Dublin hospital. Methods-Patients with Braunwald IIIA unstable angina and non-Q wave myocardial infarction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
0
11

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(86 citation statements)
references
References 26 publications
(21 reference statements)
7
68
0
11
Order By: Relevance
“…Nevertheless, clincal data exists that elevated serum VCAM-1 can be observed in patients with arterial hypertension and the relation can be drawn between the serum concentration of VCAM-1 and the advancement of atherosclerosis [9]. The studies of Semaan and Mulvihill documented coronary artery disease coupled with elevated concentration of VCAM-1 [10,11]. Our analysis confirmed that VCAM-1 concentration is elevated in patients suffering from coronary artery disease.…”
Section: Discussionsupporting
confidence: 78%
“…Nevertheless, clincal data exists that elevated serum VCAM-1 can be observed in patients with arterial hypertension and the relation can be drawn between the serum concentration of VCAM-1 and the advancement of atherosclerosis [9]. The studies of Semaan and Mulvihill documented coronary artery disease coupled with elevated concentration of VCAM-1 [10,11]. Our analysis confirmed that VCAM-1 concentration is elevated in patients suffering from coronary artery disease.…”
Section: Discussionsupporting
confidence: 78%
“…Other putative mechanisms include activation of proinflammatory cytokines and proteins such as P-selectin and vascular cell adhesion molecule-1. 27 This upregulation may promote local tissue ischemia. In addition, bleeding, especially if severe, may lead to decreased circulating blood volume, anemia, and reduced oxygen delivery.…”
Section: Consequences Of Bleedingmentioning
confidence: 99%
“…Fibrinogen was consistently found to be associated with long-term risk 42 ; however, the power of this association differs among studies, probably because of nonreproducible analytical methods or because of the consumption of fibrinogen during the acute phases. In addition, adhesion molecules and proinflammatory cytokines have been associated with a risk of new coronary events in ischemic heart diseases (ie, intracellular adhesion molecule-1 and soluble vascular adhesion molecule-1 43,44 and tumor necrosis factor-␣ 45 ) and with clinical recurrence of symptoms. 46 -48 Biological, economic, and analytical reasons, as reported before, partially explain their limitations.…”
Section: Other Inflammatory Markersmentioning
confidence: 99%